2019
DOI: 10.1038/s41390-019-0303-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and metabolic predictors of hepatic fat content in a cohort of Italian children with obesity

Abstract: ObjectivesTo comprehensively explore metabolic and genetic contributors to liver fat accumulation in overweight/obese children.MethodsTwo hundred thirty Italian children with obesity were investigated for metabolic parameters and genotyped for PNPLA3, TM6SF2, GCKR, and MBOAT7 gene variants. Percentage hepatic fat content (HFF%) was measured by nuclear magnetic resonance.ResultsHFF% was positively related with BMI, HOMAIR, metabolic syndrome, ALT, AST, γGT, and albumin. Carriers of [G] allele in PNPLA3, [T] all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 42 publications
3
37
0
2
Order By: Relevance
“…This cross-sectional study included 230 overweight (body mass index (BMI) > 85th and < 95th percentile for age and gender) or obese (BMI ≥ 95th percentile for age and gender) [19] Caucasian children and adolescents aged 6–16 years. They were consecutively recruited at the Hepatology Outpatient Clinic of the Department of Pediatrics, Sapienza University of Rome, Italy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This cross-sectional study included 230 overweight (body mass index (BMI) > 85th and < 95th percentile for age and gender) or obese (BMI ≥ 95th percentile for age and gender) [19] Caucasian children and adolescents aged 6–16 years. They were consecutively recruited at the Hepatology Outpatient Clinic of the Department of Pediatrics, Sapienza University of Rome, Italy.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, nothing is known about the effects of GCKR rs1260326 and MBOAT7 rs641738 gene variants. Though we, and others, have reported that a genetic risk score (GRS) combining all these genetic variants may represent a strong predictor of the amount of liver fat content [18,19,20], its association with kidney function has not yet been tested. The demonstration of an independent role of the prosteatogenic genetic variants in favoring the deterioration of kidney function may not only highlight novel functions of these gene products, but it may also elucidate the damaging effects of an increased liver fat accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…77 Although obesity duration and severity are also associated with a decreased renal function, 78 NAFLD has been shown to be an independent predictor even after further adjustment for other metabolic risk factors and genetic polymorphisms like I148M (rs738409) of PNPLA3. 57,79 Other comorbidities that NAFLD have been associated with include obstructive sleep apnoea (OSA), 80,81 lower whole bone mineral density 82 and polycystic ovary syndrome. 83 In addition, youth-onset NAFLD has been associated with a variety of psychosocial issues as low self-esteem, psychological distress and poor quality of life.…”
Section: Comorb Id Itie S In Children With Nafldmentioning
confidence: 99%
“…They found that genetic variants contribute more strongly to fatty liver compared to IR which is a known driver of steatosis and fibrosis. Moreover, hepatic fat content variation was explained for 8.7% by metabolic factors and for 16.1% by the weighted effect of PNPLA3, TM6SF2, and GCKR variants [196]. Similarly, in a cohort of 2, 042 children Suomela et al [197], demonstrated that a combined score including BMI, insulin levels and genetic variants in PNPLA3 and TM6SF2 genes was more accurate to predict fatty liver compared to the one used in adulthood based only on BMI and insulin.…”
Section: Polygenic Risk Scores (Prss): Clinical Translation Of Geneticsmentioning
confidence: 96%
“…We firstly applied a mendelian randomization analysis and a PRS to demonstrate that hepatic steatosis promotes the full spectrum of liver disease and the impact of risk alleles in PNPLA3, TM6SF2, MBOAT7 and GCKR on liver damage is proportional to their effect on hepatic fat accumulation [28]. In keeping with these findings, Di Costanzo et al [196], evaluated the impact of genetic and metabolic variables on liver fat accumulation in a cohort of obese children. They found that genetic variants contribute more strongly to fatty liver compared to IR which is a known driver of steatosis and fibrosis.…”
Section: Polygenic Risk Scores (Prss): Clinical Translation Of Geneticsmentioning
confidence: 99%